Genome-wide acquired uniparental disomy as well as chromosomal gains and losses in an uterine epithelioid leiomyoma - Holzmann, Carsten; Markowski, Dominique Nadine; Koczan, Dirk; Helmke, Burkhard Maria; Bullerdiek, Jörn (Molecular cytogenetics, 2014)
Epitheloid leiomyoma is a rare subtype of benign smooth muscle tumors.
Gesehen am 10.08.2020